2016
DOI: 10.1159/000453153
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Lipoprotein-Associated Phospholipase A2 with Classical Risk Factors on Coronary Heart Disease: A Multi-Ethnic Study in China

Abstract: Aims: We evaluated the synergistic effect of lipoprotein-associated phospholipase A2 (Lp-PLA2) in association with classical risk factors in predicting coronary heart disease (CHD) and demonstrated the diagnostic value of Lp-PLA2 for predicting coronary stenotic lesions in subjects with CHD. Methods: Blood samples were acquired from 911 consecutive adult subjects (662 males and 249 females) from 11 ethnic groups. Lp-PLA2 plasma levels were detected using a commercially available turbidimetric immunoassay (TIA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 49 publications
1
9
1
1
Order By: Relevance
“…Lipoprotein-associated phospholipase A2 (Lp-PLA2) is a pro-inflammatory enzyme secreted by monocytes and macrophagocytes. Precious study has found that about 70% of Lp-PLA2 binds to low-density lipoprotein (LDL) particles and the residual 30% binds to high-density lipoprotein (HDL) particles (Ge et al 2016). Our study showed the positive correlation between Lp-PLA2 and LDL-C, not between Lp-PLA2 and HDL-C.…”
Section: Discussioncontrasting
confidence: 45%
“…Lipoprotein-associated phospholipase A2 (Lp-PLA2) is a pro-inflammatory enzyme secreted by monocytes and macrophagocytes. Precious study has found that about 70% of Lp-PLA2 binds to low-density lipoprotein (LDL) particles and the residual 30% binds to high-density lipoprotein (HDL) particles (Ge et al 2016). Our study showed the positive correlation between Lp-PLA2 and LDL-C, not between Lp-PLA2 and HDL-C.…”
Section: Discussioncontrasting
confidence: 45%
“…Finally, we could not demonstrate why Lp-PLA 2 activity only showed a correlation with an increase in systolic BP but not in diastolic BP. In addition to our study, several others have reported a positive association between Lp-PLA 2 activity and systolic BP [26][27][28]. To the best of our knowledge, the underlying mechanisms that explain why only systolic BP mostly correlates with Lp-PLA 2 activity have not been elucidated.…”
Section: Controlssupporting
confidence: 47%
“…However, there was a clear positive interaction between Lp-PLA2 and classical risk factors in predicting CAD, especially for age. The proportion of CAD attributable to the interaction between Lp-PLA2 and age was as high as 64% 19 . Therefore, the association between Lp-PLA2 and CAD observed in elderly patients may be different in young Chinese patients.…”
Section: Discussionmentioning
confidence: 98%